Zoneamento ambiental da APA do Vacacaí-Mirim de acordo com a análise da fragilidade socioambiental - Silva, Franciele da (2015)
This research sought to develop the management plan of the Environmental Protection Area of Vacacaí-Mirim, using as criteria the analysis of Environmental Fragility of the area as well as the vulnerability of identification of the population living in the APA, seeking a land-use and cover ground. For the determination of Environmental Fragility was considered the methodology proposed by Ross (1994 and 2012), considering the variables: slope, geomorphology, geology, soils and land use and vegetation cover. To determine the vulnerability used in the present methodology Menezes (2014). To include natural factors associated with the analysis of the population opted for the term Fragility Environmental. From the interpretative analysis of the generated maps, the area of the APA was compartmentalized, resulting in five areas, three of which include living areas and two that are in bad condition. Risk Use zone comprises 3% of the area, and it located in the areas that comprise the class Very High Environmental Fragility associated with a high vulnerability of the population, and is therefore an area that requires specific policies, since it presents itself as a possible disaster occurrence area. The zone of Use Control presented with the High and Medium Environmental Fragility features associated with the average degree of vulnerability and low. So, we chose this nomenclature since the area has potential to develop risk scenarios, this zone covers an area of 7% of the APA. The last area with human occupation is the Direct Use, which comprises 14% of the area, and has weak features and Very Weak Environmental Fragility associated with a Low Vulnerability and therefore, the location that best fits for areas of consolidation urban within the APA. For areas that have no occupation, these were divided into Intangible and Indirect Use Zone area. The Intangible zone occupies 34% of the APA and it are located in areas with Fragility Environmental Strong and Very Strong. Already Indirect Use zone acts as a primitive area of the buffer zone occupying 42% of the area and comprising the areas of Fragility Average, Poor and Very Poor. In support of the zoning that already exists within the limits of the APA, which is the Reserve of the Atlantic Forest Biosphere, considerations were made on the core area of this zoning prepared by the Ministry of Environment, which uses the identification of Areas Permanent Preservation, which are encompassed in the Intangible zone. The preparation of this study may subsidize the planning and priority setting in the use and occupation of the APA and can assist managers in planning the territorial occupation.